Unified methodology for characterisation of global fatigue damage evolution in adhesively bonded joints (Fracture and Structural Integrity, 2020)
The present work concentrates on the development of a methodology for evaluating the fatigue performance of single and double lap adhesively bonded joints subjected to constant or variable fatigue loading. Firstly, a methodology was developed to monitor the evolution of permanent deformation, stiffness degradation and hysteresis losses of single lap joints subjected to constant amplitude fatigue load. Hereto, the global deformation of the adhesive joint was monitored using the digital image correlation technique (DIC). A MATLAB code was developed to evaluate and visualize the stiffness degradation and energy dissipation (hysteresis loops) occurring during a complete fatigue test. Secondly, this methodology was optimized to evaluate the properties of double lap joints with two different bond line thicknesses. The results of both constant and variable amplitude fatigue tests show the relation between stiffness degradation and increase in hysteresis losses with increase in number of fatigue cycles or thus fatigue damage
Keywords: Single lap adhesive joint; double lap adhesive joint; Fatigue test; hysteresis